Pengembangan Sistem Informasi Pelayanan Surat Keterangan Studi Kasus: Pemerintah Desa Legundi Kecamatan Karangjati Kabupaten Ngawi - Tio Renndy Winarna; Ismiarta Aknuranda; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Legundi village is located in Kecamatan Karangjati Kabupaten Ngawi East Java. In Legundi government case, public service such as Certificate document administration is still has a lot of troubles and to apply for a Certificate document the applicant must come to the village office. To finish the problem is needed an instrument information system that resolve the certificate and others documents. This research done to know the development of Sistem Informasi Pelayanan Surat Keterangan can be run. To solve the problem it has to do the business process modeling, requirements analysis, design and implementation of information service system certificate by applying an object-oriented approach. After that the implementation of the system will be tested to find does the system can run as the requirements that have been identified. Business process modeling activities produce the As-Is business process model and To-Be business process model, the requirements analysis yields identification of system requirements, as well as visualization of system capabilities in use case diagrams. The result of system design constitutes the documentation of object interaction model into sequence diagram, object model in class diagram, database design, interface design and pseudocode. The result of the implementation constitutes a web-based of Sistem Informasi Pelayanan Surat Keterangan tested and shows the results that the system can run in accordance with the requirement that has been identified previously.